Pure and hybrid crowds in crowdfunding markets - Liang Chen; Zihong Huang; De Liu (Financial Innovation, 2016)
Background: Crowdfunding has risen rapidly as a way of raising funds to support projects such as art projects, charity projects, and new ventures. It is very important to understand how crowds in the crowdfunding market are organized to carry out various activities. This study documents and compares two crowd designs for crowdfunding, namely pure crowds, where all crowd members participate as equals, and hybrid crowds, where crowd members are led by an expert investor. The hybrid design is rarely studied in the crowdfunding literature despite its large presence in equity crowdfunding. Methods: We examine industry practices from various countries in terms of crowd designs, review relevant literature on this topic, and develop a conceptual framework for choosing between pure and hybrid crowds. Results: We identify several inefficiencies of pure crowds in crowdfunding platforms and discuss the advantages of hybrid crowds. We then develop a conceptual framework that illustrates the factors for choosing between pure and hybrid crowds. Finally, we discuss the issue of how to manage and regulate lead investors in hybrid crowds. Conclusions: Pure crowds have several shortcomings that could be mitigated by a hybrid crowd design, especially when the proposed project suffers from greater risks, a high degree of information asymmetry, concerns about information leakage, and a high cost of managing the crowds. But for the hybrid crowd to work well, one must carefully design mechanisms for lead investor selection, compensation, and discipline. Our study contributes to the crowdfunding literature and to crowdfunding practice in multiple ways.
Keywords: 650; Crowdfunding; Prosocial lending; Rivalry relationship; Lending decision